Simone de Beauvoir: entre la vindicación y la crítica al Androcentrismo - Amorós, Celia (Investigaciones Feministas (Feminist Research), 2009)
The paper tries to situate Simone de Beauvoir’s feminist work within the tradition of feminist theory. We consider her work to be a bridge between Enlightment feminism and the so named Second Wave of the Feminist Movement. The paper does a philosophical grounding of the cycle of vindications and points out the critiqueof androcentrism.